If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 10 = 3y Reorder the terms: 10 + 2y = 3y Solving 10 + 2y = 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 10 + 2y + -3y = 3y + -3y Combine like terms: 2y + -3y = -1y 10 + -1y = 3y + -3y Combine like terms: 3y + -3y = 0 10 + -1y = 0 Add '-10' to each side of the equation. 10 + -10 + -1y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1y = 0 + -10 -1y = 0 + -10 Combine like terms: 0 + -10 = -10 -1y = -10 Divide each side by '-1'. y = 10 Simplifying y = 10
| 0=2w^2-3w-44 | | 8(-8+8k)=-192 | | 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k | | 3/4*x=2/7 | | 25x+71=156 | | 4(7x+8)+x=206 | | 2t=lb | | 6r=60 | | 3x+1+58x+33x=115 | | 75s=195 | | 2(-3)+2(-1)-(-3)(-1)+21= | | 3x+1+58x+13x=115 | | x(9+8)=33 | | =11.6 | | Y/3-3=-11 | | 12x+3=3(2x+6) | | 405.36=230+0.64x | | u+6u=14 | | -9+3v=v+3 | | x-3=-3-10x+7x | | -13+5x=x-1 | | 10n+15=9n+6n |